Constraints and challenges of financial institutions in Bangladesh: A possible way out - Alif, Tasin (Journal of Management, Economics, and Industrial Organization, 2021)
For a country like Bangladesh, ensuring financial access to all level of business, entrepreneurship and individual should be a critical priority. In the development of any country, a well trusted financial system is a prerequisite. Non-Banking Financial Institutions (NBFIs) were established for meeting the special and growing financial needs of the country. Only a few of NBFIs are running their operation effectively. One of the listed NBFIs, People’s Leasing , are currently on liquidation due to the collapse of its financial condition in the last several years. The NBFIs sector is new and small as compared to Banks, the event of liquidation is the first event of liquidation in this sector which made this sector vulnerable. Many more NBFIs are already at stake, which could be subject to liquidation or similar types of actions in the near future. This paper examined all the listed NBFIs and found that more NBFIs may face the same types of regulatory risk as like as the PLFSL in the near future. Finding alternative sources of funds should be a priority of this industry as the higher cost of funds continues to rise over the years. In 2018, the cost of weighted average fund of NBFIs was 70% upper than Banks. The Non-performing Loan (NPL) of NBFIs is continuously increasing. At the end of 2018, their NPL raised at 7.77% of their overall Leases, loans and advances. This paper shows that the retained earnings of listed NBFIs industry, is in decreasing trend over the last five years, their retained earnings goes down to negative in 2017 at 1.68 billion and at the end of 2018 it was negative 2.90 billion. After the liquidation of PLFSL, a systemic risk was evolved in the industry. Investors and depositors are confused about whether to keep their investment or not. Annual growth of deposit falls to 5.86 % in 2018. This sector also experienced a negative trend of NIM from the last five years. Also, some NBFIs are experiencing negative Interest rate spread (IRS). NBFIs are engaged in direct competition with the banks now, specially, after banks entry in the leasing activity. NBFIs firstly come into seen with the leasing products but currently the overall leasing activities of NBFI industry is at the level of 13.6 %. The annual growth of total asset was not satisfactory due to the fall of the growth rate of their asset in 2018. Total asset as compared to GDP was also reduced to 2.75% (2018) from 3% of 2017. This sector may be able to act significantly in our financial sector if we can handle the current situation. If this sector is given appropriate support for overcoming their condition, this sector can also be a sustainable sector.
Keywords: financial sector; financial institutions; non-banking financial institutions; Bangladesh